1996
DOI: 10.1111/j.1559-1816.1996.tb01123.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Client‐Directed Aggressive and Nonclient‐Directed Aggressive Work Behavior With Self‐Control1

Abstract: Employees (N= 121) participated in this study of aggressive work behavior. Employees completed a performance‐based test of self‐control. Aggressive work behavior data were then collected over a 4‐year period. Self‐control was related to client directed physically aggressive and nonclient‐directed aggressive behavior. Findings of this study provide evidence on the usefulness of self‐control in understanding aggressive work behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Burton, Cullen, Evans, Alarid, and Dunaway (1998) found that the gender gap in crime became nonsignificant when self‐control was controlled, which suggests that self‐control plays a powerful mediating role. Using a maze performance task as an index of self‐control, Latham and Perlow (1996) concluded that people with high self‐control, assessed with the Porteus Maze Test (Porteus, 1965), were less aggressive toward other people in the workplace.…”
Section: Interpersonal Relationshipsmentioning
confidence: 99%
“…Burton, Cullen, Evans, Alarid, and Dunaway (1998) found that the gender gap in crime became nonsignificant when self‐control was controlled, which suggests that self‐control plays a powerful mediating role. Using a maze performance task as an index of self‐control, Latham and Perlow (1996) concluded that people with high self‐control, assessed with the Porteus Maze Test (Porteus, 1965), were less aggressive toward other people in the workplace.…”
Section: Interpersonal Relationshipsmentioning
confidence: 99%
“…Only 1 to 2% of the employees have admitted to committing an act of physical aggression (Boye and Wasserman, 1996;Slora, 1991). Nevertheless, Latham and Perlow (1996) have shown that, during the year in which they studied a population of health care professionals in psychiatry, 12% of them were dismissed for having subjected the patients to violent treatment.…”
Section: Prevalence Of Physical Violencementioning
confidence: 99%
“…However, proportional estimates for certain counterproductive workplace behaviors, like workplace violence, are comparable to those for sexual assault perpetration involving military personnel (e.g., Budd, Arvey, and Lawless, 1996;Latham and Perlow, 1996;Merrill, Thomsen, et al, 2001). Thus, sexual assault perpetration may be considered to be at least as infrequent a behavior as certain other counterproductive workplace behaviors.…”
Section: Sexual Assault Perpetration Estimatesmentioning
confidence: 99%
“…Notably, employment screening and integrity testing research focus on counterproductive workplace behaviors, such as workplace violence. It is difficult to determine the prevalence of these behaviors, but researchers have considered certain counterproductive workplace behaviors, including workplace violence, to be infrequent (e.g., Dalton and Metzger, 1993;Grubb et al, 2005;Latham and Perlow, 1996;Murphy, 1987). Assertions that these are infrequent, or low-base-rate, behaviors tend to focus on the estimated proportion, not the number, of employees involved in the acts.…”
Section: Sexual Assault Perpetration Estimatesmentioning
confidence: 99%